Endothelial Function and Vascular Properties in Children with Sickle Cell Disease. Issue 8 (3rd December 2014) - Hadeed, Khaled; Hascoet, Sébastien; Castex, Marie‐Pierre; Munzer, Caroline; Acar, Philippe; Dulac, Yves
<x xml:space="preserve">Abstract</x> Background Sickle cell disease (SCD) is an inherited disorder characterized by recurrent painful crises with ischemia resulting from vascular occlusion. Adults with SCD have increased arterial stiffness and reduced flow‐mediated dilation (FMD), due to impaired release of substances such as nitric oxide. Aim We aimed to assess the vascular properties of carotid and brachial arteries in children with SCD compared with a control group without cardiovascular risk factors. Methods Thirty patients with SCD, mean age 12.3 ± 4.5 years, were prospectively enrolled. A control group was made up of 30 age‐ and gender‐matched healthy subjects. Carotid intima–media thickness (IMT), cross‐sectional compliance (CSC), cross‐sectional distensibility (CSD), diastolic wall stress (DWS), incremental elastic modulus (Einc), and FMD were determined in both groups. Results There was no significant difference in FMD between the two groups (8.2 ± 5.0% in the SCD group vs. 9.3 ± 4.2% in the control group, P = 0.15). There was no significant correlation between FMD and age, hemoglobin, LDH level, or transcranial Doppler findings. CSD was significantly elevated in the SCD group (0.96 ± 0.44 vs. 0.59 ± 0.21, P = 0.0002), whereas DWS and Einc were significantly lower in the SCD group. CSC did not differ significantly between the two groups. Conclusions Children with SCD have no marked endothelial dysfunction or change in arterial stiffness. These manifestations may be related to disease severity and duration. Changes may become evident later in life as the disease progresses.